Helminth component community of the paradoxal frog Pseudis platensis Gallardo, 1961 (Anura: Hylidae) from south-eastern Pantanal, Brazil - Campiao, Karla Magalhaes; da Silva, Reinaldo Jose [UNESP]; Ferreira, Vanda Lucia (Springer, 2010)
The importance of understanding the role of parasites in ecosystems and the structure of parasite communities was addressed by studying the helminth component community of the paradox frog Pseudis platensis. Thirty-two specimens of P. platensis were collected in the south-eastern Pantanal, State of Mato Grosso do Sul, Brazil, in March 2006 and April 2008, then surveyed for helminth parasites. The component community was composed of eight species: the trematodes Catadiscus propinquus, Catadiscus sp., Glypthelmins palmipedis, two metacercariae of undetermined species, the nematodes Cosmocerca podicipinus and Rhabdias sp., and an encysted larva. Catadiscus sp. dominated in the community with high prevalence (85.4%) and Berger Parker Index (0.75). Glypthelmins palmipedis was the second most prevalent and abundant species, while C. podicipinus and Rhabdias sp. were each found in only one host specimen. The high abundance of digeneans may be explained by the aquatic lifestyle of P. platensis. The helminth species found in this study were reported to infect other host species, corroborating the hypothesis that amphibian parasite communities are composed of generalist species. Pseudis platensis is a new host record for C. propinquus, C. podicipinus, and Rhabdias sp.